The underground railroad [videorecording (DVD)] - Jenkins, Barry, 1979- (Criterion collection, 2024)
Cora, fleeing slavery, embarks on a treacherous quest for freedom and is menaced by violence, supported by a clandestine community fighting for liberation, and haunted by the people she loses along the way.